Stigma Theory of the Future of the Elderly in Indonesia and Its Problems - Heriyanti, Lesti; Wijayanti, Ayu; Fitriana, Elsa; Soranti, Bouga; Maryani, Sari (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2025)
The elderly or elderly group is part of the demographic structure of a country, including Indonesia. This research aims to investigate in depth the dynamics of stigma towards the elderly in Indonesia in the future, taking into account factors of social, cultural and technological change. The research approach used is qualitative with descriptive analysis. The analysis tool used is SWOT. The research results show that stigma towards the elderly is still dominant, with the perception that the elderly are an unproductive group and are a burden on the family. In addition, there are differences in perceptions between the younger and older generations, as well as the influence of social and technological changes on the development of stigma in the future. Therefore, this research not only provides an understanding of current conditions, but also opens up insight into possible changes in stigma towards the elderly along with social, economic and technological developments.